2008
DOI: 10.1111/j.1365-2362.2008.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness in relation to subclinical atherosclerosis

Abstract: The indices of subclinical atherosclerosis, arterial stiffness and wave reflection, indicate different aspects of vascular status in otherwise healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 27 publications
(33 reference statements)
3
39
1
Order By: Relevance
“…Previous study by Wykretowicz et al (2009) found that SI DVP was not correlated to CIMT. Another study found that among Japanese subjects there was a significant correlation between b/a ratio with CIMT but this correlation was weak (β=0.069) (Tabara et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…Previous study by Wykretowicz et al (2009) found that SI DVP was not correlated to CIMT. Another study found that among Japanese subjects there was a significant correlation between b/a ratio with CIMT but this correlation was weak (β=0.069) (Tabara et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…Both parameters can be easily measured using noninvasive techniques and have been used in numerous basic and clinical studies thus far; indeed, it has even been stated that E/e' >15 is the best single indirect predictor of elevated LV filling pressure and LV diastolic dysfunction. 7,20 The lack of adjustment of our findings to mean arterial pressure, age, and heart rate as well as diabetes or used medications might be considered as the third potential limitation. However, as we have seen, the 5-covariate model is the largest model possible in this study in view of the sample size.…”
Section: 1424-27mentioning
confidence: 95%
“…In addition, in view of its correlation with coronary atherosclerosis and its capacity to predict incident coronary events, carotid IMT has been proposed as a surrogate marker of coronary atherosclerosis (10). Also pulse wave velocity (PWV) measured by tonometry provides a noninvasive estimate of arterial stiffness and is an independent predictive risk factor for all-cause mortality and cardiovascular mortality (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%